Enzootic calcinosis in horses grazing Solanum glaucophyllum in Argentina. (March 2018) - Odriozola, Ernesto R.; Rodríguez, Alejandro M.; Micheloud, Juan F.; Cantón, Germán J.; Caffarena, Rubén D.; Gimeno, Eduardo J.; Bodega, José J.; Gardey, Pedro; Iseas, Fortunato B.; Giannitti, Federico
Solanum glaucophyllum, a toxic plant known for its calcinogenic effects, causes enzootic calcinosis in ruminant and monogastric animals. We describe an outbreak of enzootic calcinosis that occurred in a herd of 110 horses grazing pastureland heavily contaminated with S. glaucophyllum in Buenos Aires province, Argentina. Ten horses developed clinical signs, and 6 horses died. Clinical signs included abnormal gait (stiff-legged action, short strides), stiffness, thoracolumbar kyphosis, reluctance to move, wide stance, chronic weight loss, weakness, recumbency, and difficulty standing. Autopsy of 2 horses revealed severe mineralization of the aorta, pulmonary arteries, heart, and lungs, consistent with enzootic calcinosis. Although horses usually have very selective grazing behavior, under food restriction conditions, they can ingest the toxic plants and can develop the disease. Enzootic calcinosis should be considered as a differential diagnosis in horses grazing S. glaucophyllum –invaded pasturelands with compatible clinical signs and lesions.